IMPLEMENTASI KURIKULUM MERDEKADALAM METODE PEMBELAJARAN SENI BUDAYA (TEATER)DI KELAS X FASE E SMA NEGERI 1 X KOTO KABUPATEN TANAH DATAR - Ayu Yolanda Putri; Tulus Handra Kadir (Universitas Negeri Padang, 2025)
This research aims to describe cultural arts (theatre) learning in class X Phase E at SMA Negeri 1 X Koto. This type of research is qualitative with a descriptive approach. The instruments used are the researchers themselves, assisted by writing tools and a camera. Data was collected through observation, interviews and documentation. Steps for data analysis include data collection, data reduction, data presentation and conclusion drawing. The research results show that Project Based Learning (PBL) is a learning method that emphasises the active involvement of learners through real projects to develop knowledge competencies, skills, and attitudes. However, in practice, the implementation of the PBL method in class X.E.4 faced failure, as the students were unable to carry out PBL properly. The application of the Hands-On Learning method in the Arts and Culture learning, particularly on the Traditional Randai Theatre material in class X.E.4, showed very positive and transformative results. One piece of evidence of the success of this method is the success of the X.E.4 students in presenting the Randai performance on the school art stage. Students not only succeeded in the process but also demonstrated concrete results in the form of creative, cohesive, and high artistic value performances. The Hands-On Learning method has proven to be highly effective in enhancing engagement, understanding, and student motivation. In the context of Cultural Arts education, this method can shift the learning paradigm from passive to active, enjoyable, and meaningful. Not only does it improve academic achievement, but this approach also supports the growth of character, creativity, and social relations among students. Therefore, this method is highly worthy of continued development and sustainable application, particularly in learning that requires contextual and participatory understanding.